2016
DOI: 10.1111/cen.13163
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma and paraganglioma in patients with neurofibromatosis type 1

Abstract: We recommend patients with NF1 have biochemical case detection testing for PHEO/PGL every 3 years starting at age 10 to 14 years. Biochemical case detection testing should also be carried out prior to elective surgical procedures and conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
2
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 16 publications
1
91
2
12
Order By: Relevance
“…The two largest reported series for neurofibromatosis type 1 (NF 1)-associated pheochromocytoma are the Freiburg International NF 1 pheochromocytoma study and the Mayo Clinic pheochromocytoma and PGL registry (Bausch et al 2006, Gruber et al 2017. Only 2% of patients in the Freiburg study, and 1.2% of patients in the Mayo Clinic registry, have symptomatic paraganglial tumors and NF 1.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…The two largest reported series for neurofibromatosis type 1 (NF 1)-associated pheochromocytoma are the Freiburg International NF 1 pheochromocytoma study and the Mayo Clinic pheochromocytoma and PGL registry (Bausch et al 2006, Gruber et al 2017. Only 2% of patients in the Freiburg study, and 1.2% of patients in the Mayo Clinic registry, have symptomatic paraganglial tumors and NF 1.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…Phaeochromocytoma in NF1 is unilateral and intra-adrenal in more than 80%, and has a malignant rate of about 10%. [7][8][9][10][11] Available guidelines suggest screening for the condition with urinary or serum metanephrines only when typical symptoms are present. [12][13][14] The most common symptoms of phaeochromocytoma are hypertension, headaches, palpitations and diaphoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, systematic screening of patients with NF1 for phaeochromocytoma increases the detection rate, as many are asymptomatic or lack a family history of chromaffin tumours, and are diagnosed by symptomatology or incidentally. Illustrating this point, Gruber and colleagues noted a prevalence of 6·6 per cent in a subset of patients undergoing case detection screening; in another series, Képénékian et al . reported that 66·7 per cent of patients with NF1 and hormonally active tumours (84 per cent of all those with phaeochromocytoma) were asymptomatic and would have remained undetected without screening.…”
Section: Nf1 Mutations In Neurofibromatosis Typementioning
confidence: 99%
“…NF1‐associated phaeochromocytomas resemble apparently sporadic tumours in terms of age at presentation, and often negative family history for phaeochromocytomas, but NF1‐related bilateral adrenal disease occurs in 11–27 per cent of patients with phaeochromocytoma. Although the value of subtotal adrenalectomy for patients with NF1 might be questionable owing to the low general penetrance for phaeochromocytomas, those who develop adrenal neoplasms are also more likely to have bilateral disease, implying the existence of either phaeochromocytoma‐prone NF1 mutations or other modifying factors; these should be considered key subjects for further investigation.…”
Section: Nf1 Mutations In Neurofibromatosis Typementioning
confidence: 99%
See 1 more Smart Citation